PENGARUH SISTEM PENGENDALIAN INTERNAL DAN PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - Taufiqurrohman (Universitas La Tansa Mashiro, 2025)
The purpose of this study is to examine the effect of the implementation of internal control system and accounting information system to the quality of financial reports of regional device organization(OPD) in the Government of Kabupaten Lebak. The population of this study isthe regional servicesin the environment of Government of Kabupaten Lebak (15 OPD) with 45 respondents. The data and informations needed for this research are collected by conducting field research. The data used in this research is primary data and data collection is done directly by using questionnaires.The method used for determining the sample is purposive sampling method. Based on statistical analyzing using SPSS (Statistical Package for the Social Sciences). The results of the research are either simultaneously or partially support the hypothesis that the implementation of internal control system and accounting information system affect the financial reports of regional device organization(OPD) in the Government of Kabupaten Lebak.